La banalización de la prescripción de psicofármacos en un ambulatorio de salud mental - Ferrazza, Daniele de Andrade (2010)
The development of modern psychiatric medications coupled with the wide range currently gained by preventive emphasis in mental health changed the practices of psychiatry, which is no longer focused on treating insanity but is also dedicated to treat any psychiatric suffering through the prescription of psychopharmacos. This study discusses the current process in which medication has been generalized, and presents the results of an exploratory study aimed to examine the patients' medical files, the trajectory of users since they enter the service to the prescription of psychiatric medication in the scope of a Mental Health Outpatient Clinic, in a town in the west of the São Paulo state, Brazil. Results revealed that most (65%) users already arrive at the service with previous prescription of psychiatric medications, and nearly all (99%) of them receive prescriptions of psychiatric medication once forwarded to psychiatric consultations.